Narrating confinement: "Liberation", a tragic and prison story from Escalas by César Vallejo - Barreto Quiche, Miguel Ángel (2020)
The purpose of this paper is to develop a textual analysis of "Liberación", a story that is part of César Vallejo's narratives collected under the title of Escalas (1923), a work printed at the Talleres Tipográficos de la Penitenciaría de Lima (Lima Penitentiary Typographical Workshops). In "Liberación" we note common topics for the narrative construction of the prison experience, such as injustice, memory and fear. We observe that these topics metaphorize confinement as an insufferable and hopeless space, mainly for Jesús Palomino, the protagonist, whose tragic states or psychological disturbances increase as a result of confinement. Our analysis concentrates on exploring the protagonist in the scenes influenced by these three topics.